THE IMPACT OF PADLET AS A DIGITAL TOOL ON VOCABULARY ACQUISITION AMONG YEAR 4 ESL PUPILS - Zulmaidi, Fatimah Az-Zahrah; Sulaiman, Nur Ainil (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study examines the effectiveness of Padlet in enhancing vocabulary acquisition among Year 4 ESL pupils in a Malaysian primary school. Using a quasi-experimental mixed-methods design, 30 pupils completed a pre-test and post-test and participated in a four-week Padlet-based intervention involving interactive and multimodal vocabulary tasks. Quantitative results showed a significant improvement in vocabulary performance, with mean scores increasing from 9.8 to 17.9 (t = 18.62, p < .001). Qualitative data from classroom observations and interviews indicated strong pupil engagement, enjoyment and motivation. Learners reported that Padlet’s visual features, multimedia support and collaborative functions made vocabulary learning easier, more meaningful and more memorable. The findings demonstrate that Padlet effectively supports vocabulary recognition, recall and usage, aligning with principles of Constructivist Learning Theory, Multimedia Learning Theory and the Technology Acceptance Model. This study provides empirical evidence for integrating digital tools in Malaysian primary ESL classrooms to promote interactive and learner-centered vocabulary instruction.